48.6k views
7 votes
Which of the following is an equivalent

simplified expression for
3(2x + 1) - 2(4x - 1)
A. 2x + 1
B. -2x + 5
C. -X + 5
D. 14x + 1
E. 14x - 1

2 Answers

10 votes

Answer:

it is B

Explanation:

3*2x=6x

2*4x=8x

1*3=3

1*2=2

6x-8x= -2x

3+2=5

i got the +2 because there are two negative signs and that makes it positive

User Joey Gao
by
5.9k points
9 votes

Answer:

B. -2x + 5

Explanation:

First, distribute the 3 and 2 to the parentheses:

3(2x + 1) - 2(4x - 1)

6x + 3 - 8x + 2

Add like terms:

-2x + 5

So, the simplified expression is -2x + 5

B is the correct answer

User Adrian Rosca
by
5.6k points